Answer:
w = -12
Explanation:
One way to solve this is to subtract the term on the left from both sides of the equation, simplify, divide by the x-coefficient, add the opposite of the constant.
0 = 8(2w+3)+16 -4(3w-2)
0 = 16w +24 +16 -12w +8 . . . . eliminate parentheses
0 = 4w +48 . . . . . . collect terms
0 = w +12 . . . . . . . . divide by 4
-12 = w . . . . . . . . . add -12
___
Alternate solution
12w -8 = 16w +24 +16 . . . . . eliminate parentheses
-8 = 4w +40 . . . . . . . . . . . . . subtract 12w (the smaller w term)
-48 = 4w . . . . . . . . . . . . . . . . subtract 40 (to get the w term by itself)
-12 = w . . . . . . . . . . . . . . . . . . divide by 4, the coefficient of w
This is about the same number of steps, and it gives you the same answer. Here, you are asked to identify the w-term you want to subtract, and the constant you want to subtract in order to get the variable and the constant on opposite sides of the equal sign. Above, we save that separation until last. Either way works. It seems likely that you're taught this "alternate solution" in school.